Is Brain-Derived Neurotropic Factor Methylation Involved in the Association Between Prenatal Stress and Maternal Postnatal Anxiety During the COVID-19 Pandemic? - Provenzi, Livio; Villa, Marco; Mambretti, Fabiana; Citterio, Andrea; Grumi, Serena; Bertazzoli, Emanuela; Biasucci, Giacomo; Decembrino, Lidia; Gardella, Barbara; Giacchero, Roberta; Magnani, Maria Luisa; Nacinovich, Renata; et al. (Frontiers in Psychiatry, 2022)
Background. The COVID-19 pandemic is a collective trauma that may expose susceptible individuals to high levels of stress. Pregnant women represent a high-risk population, considering that pregnancy is a period of heightened neuroplasticity and susceptibility to stress through epigenetic mechanisms. Previous studies showed that the methylation status of the BDNF gene is linked with prenatal stress exposure. The goals of this study were (a) to assess the association between pandemic-related stress and postnatal anxiety and (b) to investigate the potential role of maternal BDNF methylation as a significant mediator of this association. Methods. In the present study, we report data on the association among pandemic-related stress during pregnancy, maternal BDNF methylation, and postnatal anxiety symptoms. Pandemic-related stress and postnatal anxiety were assessed through self-report instruments. BDNF methylation was estimated in 11 CpG sites in DNA from mothers’ buccal cells. Complete data were available from 108 mothers. Results. Results showed that pandemic-related stress was associated with an increased risk of postnatal anxiety, r = .20, p <.05. CpG-specific BDNF methylation was significantly associated with both prenatal pandemic-related stress, r = .21, p < .05, and postnatal maternal anxious symptoms, r = .25, p = .01. Moreover, a complete mediation by the BDNF CpG6 methylation emerged between pandemic-related stress during pregnancy and postnatal maternal anxiety, ACME = .66, p < .05. Conclusions. These findings suggest that BDNF epigenetic regulation by pandemic-related stress might contribute to increase the risk of anxiety in mothers. Policymakers should prioritize the promotion of health and well-being in pregnant women and mothers during the present healthcare emergency.